Why government succeeds and why it fails. de Amihai Glazer and Lawrence S. Rothemberg Harvard University Press, Cambridge, Massachusetts, págs. 204,2001 - Etcheverrigaray (h.), Carlos F. (2001)
Fil: Etcheverrigaray (h.), Carlos F. Pontificia Universidad Católica Argentina. Escuela de Ciencias Políticas; Argentina